PENGUJIAN BLACKBOX PADA WEBSITE WORKER’S MENGGUNAKAN METODE EQUIVALENCE PARTITIONING - Derick Triady; Izmy Alwiah Musdar; Hendra Surasa (STMIK KHARISMA Makassar, 2023)
Software testing is carried out to find error that exist in the software before they are found by the user. This study discusses how to do black box testing on website worker’s, which is a website that’s provide information about job vacancies. The test method that will be used is black box testing with the equivalence partitioning method as a test case design technique. The equivalence partitioning method is a method that divides data regarding input domain into partitions, from these partitions can produce test cases. The test result show that black box testing with the equivalence partitioning method can be used to find error in software. There are 29 test case where 68% of the test case successful or passed and 32% of the test case failed.